UPAYA MENINGKATKAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN LANGSUNG PADA SISWA KELAS IV.B SD NEGERI 60 PETANI KECAMATAN MANDAU - Nursaibah Siagian; Erlisnawati Erlisnawati; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is the lack of science students' learning outcomes, as seen from the average value of students is 62.86. Of the 21 students who achieve grades above KKM just 9 students (42.86%), while students who have not yet reached KKM many as 12 people (57.14%), the value specified KKM is 70. Based on these problems is necessary to study the action class by applying direct instructional model. This research aims to improve learning outcomes grade science students IV B SD Negeri 60 Petani kecamatan Mandau school year 2014/ 2015 the number of students 21 people consisting of 10 men and 11 women. This study was conducted by two cycles. At each cycle I and II consist of three meetings, which consists of two face to face meetings and one times daily test at the end of the cycle. With direct learning model approach is applied, it can improve student learning outcomes IPA, it is seen from the increase in student learning outcomes from the base score is an average of 62.86, an increase of 12.12% to 70.48 in the first cycle, and on the second cycle increased by 39.31% to 87.38. The percentage of teacher activity also increased, as seen from the percentage of the activity of teachers in the first cycle the first meeting 65% increase in the second meeting to 75%, in the first meeting of the second cycle increased to 90% and in the second meeting to 95%. Based on the results of this study concluded that the implementation of direct learning model, can improve learning outcomes grade science students IV B SD Negeri 60 Petani kecamatan Mandau.Key Words : Use of Direct Learning Model, Science Learning Outcomes.